2006
DOI: 10.1038/ng1765
|View full text |Cite
|
Sign up to set email alerts
|

MPV17 encodes an inner mitochondrial membrane protein and is mutated in infantile hepatic mitochondrial DNA depletion

Abstract: The mitochondrial (mt) DNA depletion syndromes (MDDS) are genetic disorders characterized by a severe, tissue-specific decrease of mtDNA copy number, leading to organ failure. There are two main clinical presentations: myopathic (OMIM 609560) and hepatocerebral (OMIM 251880). Known mutant genes, including TK2, SUCLA2, DGUOK and POLG, account for only a fraction of MDDS cases. We found a new locus for hepatocerebral MDDS on chromosome 2p21-23 and prioritized the genes on this locus using a new integrative genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
399
5
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 382 publications
(419 citation statements)
references
References 30 publications
13
399
5
1
Order By: Relevance
“…Several such genes have now been described (POLG1, PEO1, TK2, DGOUK, MPV17, SLC25A4, and RRM2B) and are associated with mitochondrial disease in adults and children. [25][26][27] Other recessive nuclear mutations are known to affect structural subunits or assembly of mitochondrial respiratory chain complexes, and again these have not been included in our prevalence figures. Our clinical experience in a tertiary referral center for mitochondrial disease would suggest that approximately 75% of adultonset mitochondrial disease is a consequence of primary mtDNA mutations, whereas this figure is less than 20% for childhood presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Several such genes have now been described (POLG1, PEO1, TK2, DGOUK, MPV17, SLC25A4, and RRM2B) and are associated with mitochondrial disease in adults and children. [25][26][27] Other recessive nuclear mutations are known to affect structural subunits or assembly of mitochondrial respiratory chain complexes, and again these have not been included in our prevalence figures. Our clinical experience in a tertiary referral center for mitochondrial disease would suggest that approximately 75% of adultonset mitochondrial disease is a consequence of primary mtDNA mutations, whereas this figure is less than 20% for childhood presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between MPV17 and a hepatocerebral mitochondrial DNA depletion syndrome has been known since 2006 (Spinazzola et al 2006), when an integrative genomics strategy suggested a mitochondrial gene resided in a chromosomal region linked with hepatocerebral disease in infants. Previously, MPV17 had been thought to be a peroxisomal protein, but studies indicated that it was in fact localized to the mitochondrial inner membrane (Spinazzola et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, MPV17 had been thought to be a peroxisomal protein, but studies indicated that it was in fact localized to the mitochondrial inner membrane (Spinazzola et al 2006). Since this initial breakthrough, little additional insight has been gained into how mutations in this gene cause mitochondrial DNA depletion, or why the liver and nervous system are disproportionately affected.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30 affected individuals have been reported with MPV17-related hepatocerebral MDS [59][60][61][62][63][64][65][66][67][68]. Of note, among those confirmed cases are individuals with Navajo neurohepatopathy who were found to have homozygous p.Arg50Gln mutations in MPV17.…”
Section: Mpv17-related Hepatocerebral Mdsmentioning
confidence: 99%